YIELD AND EARLINESS IN BULKING OF SOME INTRODUCED CASSAVA GENOTYPES UNDER MOIST SAVANNA - Adu-Gyamfi, R.; Osei, C; Anadumba, E (UDS International Journal of Development, 2016)
Over the years several genotypes of cassava have been abandoned due to late bulking. It is necessary to select early bulking, high yielding genotypes for marginal rainfall areas with rising population densities as pertains in Sub-Sahara Africa. It is based on this that a study was conducted with two introduced cassava genotypes; TME225 and 92/0057 (test), and compared with two adapted varieties Afisiafi and Biabasse (control) to determine which genotypes are early and high yielding. The growth and yield parameters considered were the leaf production and canopy spread, stem size and development, root development and yield. The control genotypes produced more leaves at 24 weeks after planting (WAP) than the introduced genotypes. This reflected in the canopy spread with the introduced genotypes having lower canopy spread. The introduced genotypes, however, were higher in branching than the control genotypes by 16 WAP and the trend continued throughout the plant life. Cluster analysis identified one introduced genotype and a control variety to have a mean dry matter yield above the average of the four genotypes. Generally, the introduced genotypes were significantly earlier than the check varieties at 32 WAP in root initiation and yield. The study recommends TME225 for farmers in the Guinea savannah ecology. Keywords: Cassava Manihot esculenta, Bulking, Earliness, Savannah, Root storage